Incidence and Outcome of Second Branchial Cleft Anomalies: A Three Years Experience and Appreciation (Global Journal of Medical Research, 2020)
Background: Second branchial cleft anomalies are remarkable of all other inborn errors of branchial apparatus. As a congenital, it may be presented at birth but usually manifests in early teenagers and young adults. Like all other inborn errors, it is better to correct earlier before suffering from any complications. Methods: It is a cohort retrospective study of 15 cases in the Department of Otolaryngology and Head-Neck Surgery, Cumilla Medical College, and Cumilla Medical Centre, Bangladesh, from 01 July 2016 to 31 June 2019. Results: Incidence of anomalies among routine ENT operations was 0.21%. Of 15, the cyst was 04(26.27%), sinus was 10(66.66%), the fistula was 1(6.67%), children were 09(60%), the adult was 6(40%), and young adult and an early teenager were 07(46.66%), male was 11(75.33%), and females were 04(26.27%), bilateral were 2(13.33%), unilateral was 13(86.67%) in which right was 10(76.33%), and left was 03(23.08%), painful cyst with abscess was 01(6.67%), the painless cyst was 03(20%), sinus with the mucoid fluid discharge was 07(46.68%), painful sinus with mucopurulent discharge and skin-excoriation was 03(20%), painful fistula with mucopurulent discharge and skin-excoriation was 01(6.67%), postoperative wound infection was 2(13.33%). Recurrence and the branchio-oto-renal syndrome were absent in our study.
Keywords: second brachial cleft anomalies (SBCA); cyst; sinus; fistula